LncRNA NEAT1 promotes gastric cancer progression via miR-1294/AKT1 axis - Wu, Dianchao (Open Med (Wars), 2020)
Long non-coding RNAs (lncRNAs) were reported to promote the development of gastric cancer (GC). Nuclear-enriched abundant transcript 1 (NEAT1) played a great role in diverse cancers, but the mechanism of NEAT1 in GC remains indistinct. NEAT1 and AKT1 were distinctly up-regulated and miR-1294 was down-regulated in GC tissues and cells. Cell proliferation and metastasis were refrained but apoptosis was promoted in GC cells after knockdown of NEAT1. NEAT1 negatively regulated miR-1294 expression, and the miR-1294 inhibitor reverted the si-NEAT1-induced effect on GC cells. NEAT1 modulated AKT1 expression through miR-1294, and the si-NEAT1-induced effect was relieved by AKT1. NEAT1 affected phosphatidylinositol 3-kinase (PI3K)/AKT/mammalian target of rapamycin (mTOR) signaling pathway via regulating miR-1294 and AKT1. NEAT1 could modulate cell proliferation, apoptosis, and metastasis in GC cells by regulating the PI3K/AKT/mTOR signaling pathway via the miR-1294/AKT1 axis, showing the great potential for NEAT1 as a valid biomarker in the progression and treatment of GC.